تطبيق طريقة لعبة Make and Match لترقية مهارة القراءة لدى طالبات في المدرسة الدينية الوسطى بمعهد دار الفلاح الإسلامي الخامس جوكير جومبانج - Hanum, Laila Kamila; Rohman, Fathur (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
still struggle with reading Arabic texts and understanding their meanings accurately. Their enthusiasm for learning Arabic reading is low, largely due to traditional, non-interactive teaching methods that lead to passive learning. In response, the researcher conducted a qualitative case study titled